ANALYSIS OF SOCIO-ECONOMIC LIFE IN THE WORKS OF KOMIL KHOREZMI (Scientific journal of the Fergana State University, 2026)
This article focuses on the reflection of the socio-economic life of the era in the works of the great enlightener, poet, and scholar of the 19th century – Komil Khorezmi. The study analyzes information related to the socio-economic conditions of that time as depicted in the author’s works. Furthermore, it reveals Komil Khorezmi’s attitude toward issues such as justice, labor, science, enlightenment, and human values. The article scientifically examines the significance of the poet’s creative heritage as a historical source, as well as his style and artistic mastery in portraying the socio-economic reality of his time.